Diclosulam e sulfentrazone no manejo das plantas infestantes na cultura da soja resistente ao glifosato e efeito da palha e precipitação sobre estes herbicidas - Minozzi, Guilherme Barbosa (2014)
The Roundup Ready (RR) soybean facilitated weed management by allowing the use of glyphosate in all stages of crop development. But the continuous use of this herbicide can select resistant weed biotypes and tolerant species, suggesting the need of developing new management practices. Thus, the aim of this proposal was to evaluate the effectiveness of different managements in soybean using residual and post-emergent herbicides in the control of weeds and the interference caused by straw and rainfall on the efficacy of the herbicides diclosulam and sulfentrazone. In the first experiment, in the field, was used the randomized block design with four repetitions and 14 treatments, involving the application of glyphosate (712 g ha-1) + 2,4-D (670 g ha-1) in the burndown application of weeds, 14 days before planting soybeans, with and without the presence of residual herbicides, diclosulam (29.4 g ha-1) and sulfentrazone (600 g ha-1), and treatments with glyphosate in post emergence at a single time in stages V2 (Second fully expanded trifoliate) or V4 (Fourth fully expanded trifoliate) at the dose (712 g ha-1) or in both stages V2 and V4 (356 g ha-1 in each one). In the second trial, in the greenhouse, was used a randomized block design with four repetitions in a factorial 2 x 3 x 5, being two herbicides diclosulam (29.4 g ha-1) and sulfentrazone (600 g ha-1), three levels of corn straw on the soil surface (0, 5 and 10 t ha-1) and five simulations of 20mm of rain (without rain, 24, 72, 120 and 240 hours after application of the herbicide), each experimental unit consisted of a vase and after rain simulation was sown in pots one biomarker, which was assessed for phytotoxicity. In the field experiment, it was noted the importance of applying a residual herbicide in the burndown, to reduce applications of glyphosate in post emergence, the treatment with diclosulam and a single application of glyphosate in V4 promoted the highest soybean yield of 3484,93 kg ha-1 against 719 kg ha-1 of the untreated treatment. In green house interaction was observed between the amount of straw (which can intercept the jet sprayed) and the time of occurrence of rain after application of herbicides and in this case diclosulam proved to be less dependent of water to reach its target.